Fibre Dimorphism in Secondary Xyiem of Family Lauraceae from Erstwhile India - Gupta, Sangeeta; Kumar, Dheerendra (Indian Forester, 2020)
Secondary xylem of Forty seven species of family Lauraceae was studied for fibre dimorphism (i.e. species having both Fibres and Parenchyma-like-Fibres). These species fail under eleven genera viz. Actinodaphne, Aiseodaphne, Beiischmiedia, Cinnamomum, Cryptocarya, Dehaasia, Lindera, Litsea, Neoiitsea, Persea and Phoebe. Parenchyma-like-Fibres (PLF) were found to be present in 90% of the species of this family and have not been reported earlier. PLF were observed both in wood section and maceration. The PLF was found to be species specific. However, within a species variation with regards to amount ofPLF was observed based on which 12 categories were made. The septation in PLF was observed to be independent of fibre septation. PLF were not observed in 5 species viz. Actinodaphne tedulingami, Aiseodaphne semicarpifolia, B. fagifolia, Cinnamomum glanduliferum and C. zeylanicum. Statistical analysis inferred that the volume of fibre and volume of PLF showed significant linear correlation relationship which indicates that PLF are basically storage fibres with more lumen and lesser wall thickness and length.